Bahaya Adiksi Instagram Ditinjau dari Fear of Missing Out dan Narsisme - Wardari, Ayunda Fikri; Rasyid, Miranti (Universitas Muhammadiyah Metro, 2024)
As time goes by, everyone will be able to find information easily. You only need an application that can help you find news and information, one of which is the Instagram application. Many positive activities can be seen through Instagram, but in reality, many students use Instagram excessively. This research aims to determine the influence of fear of missing out and narcissism on Instagram addiction. This research method uses a quantitative approach. The subjects of this research were 45 Social and Political Sciences students at Mulawarman University who were selected using purposive sampling techniques. The data collection method used was the Instagram addiction scale, fear of missing out, and narcissism. The data analysis technique used is multiple linear regression. The collected data was analyzed with the help of the SPSS (Statistical Packages for Social Science) computer program version 26.0 for Windows. The research results show that: (1) there is a significant influence of fear of missing out and narcissism on Instagram addiction with p-value = 0.003 and has an influence contribution (R2) of 23.7%; (2) there is no significant influence of fear of missing out on Instagram addiction with beta coefficient (β) = 0.214, t = 1.247 < t table = 2.017, and p = 0.219 (p > 0.05); (3) there is no significant influence of narcissism on Instagram addiction with beta coefficient (β) = 0.324, t = 1.885 < t table = 2.017, and p = 0.066 (p > 0.05).